Performing Peace and Friendship : The World Youth Festivals and Soviet Cultural Diplomacy - Koivunen, Pia (Rethinking the Cold War, 2022)
Through a case-study of the World Youth Festival, the book provides new insights into the Soviet role in the cultural Cold War and offers an explanation why the USSR failed in the cultural battle against the USA and the capitalist system. With a detailed analysis of grass-roots interaction, it re-evaluates the agency of micro-level actors and argues that individuals had more chances for transnational contacts than previous scholarship has shown